Hydrogen Sulfide Ameliorates Homocysteine-Induced Cardiac Remodeling and Dysfunction - Kar, Sumit; Shahshahan, Hamid R.; Kambis, Tyler N.; Yadav, Santosh K.; Li, Zhen; Lefer, David J.; Mishra, Paras K. (Frontiers in Physiology, 2019)
Patients with diabetes, a methionine-rich meat diet, or certain genetic polymorphisms show elevated levels of homocysteine (Hcy), which is strongly associated with the development of cardiovascular disease including diabetic cardiomyopathy. However, reducing Hcy levels with folate shows no beneficial cardiac effects. We have previously shown that a hydrogen sulfide (H2S), a by-product of Hcy through transsulfuration by cystathionine beta synthase (CBS), donor mitigates Hcy-induced hypertrophy in cardiomyocytes. However, the in vivo cardiac effects of H2S in the context of hyperhomocysteinemia (HHcy) have not been studied. We tested the hypothesis that HHcy causes cardiac remodeling and dysfunction in vivo, which is ameliorated by H2S. Twelve-week-old male CBS+/− (a model of HHcy) and sibling CBS+/+ (WT) mice were treated with SG1002 (a slow release H2S donor) diet for 4 months. The left ventricle of CBS+/− mice showed increased expression of early remodeling signals c-Jun and c-Fos, increased interstitial collagen deposition, and increased cellular hypertrophy. Notably, SG1002 treatment slightly reduced c-Jun and c-Fos expression, decreased interstitial fibrosis, and reduced cellular hypertrophy. Pressure volume loop analyses in CBS+/− mice revealed increased end systolic pressure with no change in stroke volume (SV) suggesting increased afterload, which was abolished by SG1002 treatment. Additionally, SG1002 treatment increased end-diastolic volume and SV in CBS+/− mice, suggesting increased ventricular filling. These results demonstrate SG1002 treatment alleviates cardiac remodeling and afterload in HHcy mice. H2S may be cardioprotective in conditions where H2S is reduced and Hcy is elevated.